Data modelling and the audit. (2015) - Gal, Graham
The development of a corporate-wide data model is a tool to integrate firm's data. The lack of staff is an impediment to data management efforts. Creation of a comprehensive data-model includes collecting and verifying extensive meta-data information. Meta-data includes provenance (both processes and code), structure, relationships among data, data transformation, and units responsible for data items. Inclusion of meta-data will enhance data quality and provide support for users' data understanding and use. The more complete and detailed the corporate data model, the better information can be communicated across the organisation. This meta-data can be an explicit representation of management policies. For instance, employee type with rights to enter or manipulate data elements and the skill and knowledge requirements. These policies can also represent internal controls. This paper examines management policies within data-models and use of this information to test audit assertions on the effectiveness, design, and operation of internal controls.